A alfabetização científica: ensino de Ciências Naturais no Ensino Fundamental da Rede Municipal de Educação de Jaraguá do Sul - SC - Vendruscolo, Anadir Elenir Pradi (2016)
This study aimed to examine how Scientific Lliteracy materializes in science teaching os the 4th grade of elementary school in the municipal education in Jaragua do Sul (SC). It was guided by a qualitative approach, starting with the national and international literature review of the science education curriculum on the Scientific Literacy and on the curricular and methodological processes involving the action of teaching and learning in this area. Documentary analysis of official guidelines from Ministry of Education (MEC) for the teaching of Science, of guiding documents of the Municipal Jaraguá do Sul Education (SC), the pedagogical projects and lesson plans for teachers working in 4th. Grade in the five schools, the investigated field of this research, as well as interviews and questionnaires were the tools for data collection. Theoretical references as Moraes (1999), Laugksch (2000), Krasilchik (1987; 1992), Shen (1975), Lorenzetti (2001), Delizoicov (2002), Chassot (2001), Nardi (2014), Borges (2010 ), Nascimento et. al. (2010), Azevedo (2006), especially Sasseron (2008) and Schiel (2005) were used for theoretical approaches in education of Sciences and Scientific Literacy indicators, as well as in research methodology. So was the theoretical frameworks of Feldmann ( 2005), Sacristan (2001) and García on curriculum and teacher training. Thus, it was not possible to make it clear that the conception of scientific literacy is present in the guidelines for the teaching of science to guide the teacher to use the investigative methodologies for the development of the classes. The analyzed data have recognized that the planning of classes despite having numerous activities and variety of educational resources does not have investigative activities to explicitly detect the Scientific Literacy indicators consistently for its development. The planning, pedagogical advice, knowledge of the area of natural sciences, the use of available resources, the methodological choices adopted by the teacher, presented themselves as founding elements for the process of Scientific Literacy. It was also observed the need for improvement in initial and continuing training processes of teachers who work in the early years of elementary school. It is believed that the survey will provide support for the development and improvement of teaching practice, teaching and learning in the area of Natural Sciences, committed to the promotion of Scientific Literacy, essential for the formation of more aware and critical citizens